TroCCiBras and its partner projects HIBISCUS and TROCCINOX: The 2004 field campaign in the state of São Paulo - Held, Gerhard [UNESP]; Pommereau, Jean-Pierre; Schumann, Ulrich (My University, 2008)
This overview paper summarizes the objectives of the Tropical Convection and Cirrus Brasil project, as well as those of the European Commission sponsored HIBISCUS and TROCCINOX projects, which conducted a joint field campaign in the State of São Paulo from January to March 2004. Emphasis is given on the description of different types of lidars and their deployment for obtaining meteorological data during the joint field campaign in 2004. © Sociedad Española de Óptica.
Keywords: Airborne H 2O DIAL; Balloon-borne micro-lidar; Brazil; Elastic backscatter lidar; HIBISCUS; Radar observations; State of São Paulo; TroCCiBras; TROCCINOX